How to talk about science in ways that are comprehensible and interesting? Evaluation of an evidence-based science communication training program for graduate students - Fick, Julian; Hendriks, Friederike; Thies, Barbara (Frontiers in Education, 2025)
IntroductionIn order to graduate, students in higher education need to acquire a diverse set of competencies, among them mastering communicative competencies and skills. However, training in science communication usually is not embedded in formal education programs and existing training programs are often insufficiently or not at all evaluated. We developed an evidence-based science communication training aiming to foster students’ abilities in communicating about research comprehensively and in a way that better involves interlocutors. We evaluated the training‘s effectiveness in increasing students’ attitudes, self-efficacy beliefs, knowledge and actual science communication performance.MethodsWe implemented a pre-post summative evaluation design. The sample consisted of 44 master’s students from different disciplinary backgrounds.ResultsThe participants were highly satisfied with the training. Their self-efficacy beliefs, self-rated abilities, knowledge, and favorable attitudes regarding strategies to enhance involvement increased. Strategy use in communication performance was measured by analyzing transcribed recordings of short video presentations. While use of comprehensibility-strategies remained on a high level, involvement-strategy use increased.DiscussionWe provide evidence for the effectiveness of our training program. Furthermore, we suggest an operationalization of basic science communication competencies and discuss challenges regarding the behavioral assessment of actual science communication performance, as well as the limitation of not having had a control group.